MODEL PERILAKU INOVATIF INDIVIDU DALAM PENGGUNAAN PASCA ADOPSI TEKNOLOGI INFORMASI - Sigit Pramono (Manajemen Bisnis, 2012)
Sigit PramonoUniversitas Muhammadiyah MalangE-mail: sigitpramono_03@yahoo.comABSTRACTThe aim of this study was to confirm the relationship between variables that allegedly affect the postadoptionbehavior of technology in business organizations based on information technology (IT) Post-adoptionbehavior investigated was to innovate with IT that appears on the stage of infusion. The object ofresearch was paperless office internal (POINT) at PT. Telekomunikasi (Telkom), Indonesia, Tbk. Datawas collected from permanent employees of PT. Telkom Indonesia in four locations whose usingPOINT application shaped by internal web-based portal. Data collected by using questionnaires inthe period December 2010 to January 2011. Respondent were 118 workers. Data analysis was performedusing a model of Structural Equation Modeling (SEM) with component-based applicationassistance SmartPLS 2.0. The results state that user satisfaction, personal innovative and facilitatingconditions were positively related directly to innovate with IT. Post-adoption perceived usefulnessand confirmation of expectations were positively related indirectly to innovate with IT, while selfefficacyand rewards found no effect on innovate with IT. The result of research confirmed previousresearch and conducted discussions on the results of research that was unique. Discussion and conclusionsof study yields several implications and needed further research on the behavior of innovatingwith IT.Keywords: Innovate with IT, the post-adoption behavior, personal innovativeness, self-efficacy, rewards